Current situations of vietnam companies’ trade Defense lawsuits and some proposed solutions - Nguyen, Dang Tuan Minh (2020)
In the period of struggle economy, how to protect justifiable rights of exporters in global market is a big question for authorized agents to research and find solutions. This thesis is aimed at analysing some main reasons for the increase of lawsuits involving Vietnamese exporters and various compatible solutions to limit legal risks. Besides, the document also clarify the importance of managing practise in VCA, Ministry of Industry and Trade and relating legal authorities and more vital, enhance the awareness and responsibility of domestic enterprises and individuals to be self- protective from global economy integration.